1998
DOI: 10.1034/j.1399-3054.1998.1030316.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of nitrogen remobilization in defoliated Phleum pratense and Festuca pratensis under short and long photoperiods

Abstract: The impact of photoperiod on the rate and magnitude of N remobilization relative to uptake of inorganic N during the recovery of shoot growth after a severe defoliation was compared over 18 days in two temperate grass species, timothy (Phleum pratense L. cv. Bodin) and meadow fescue (Festuca pratensis Huds. cv. Salten). Plants were grown in flowing solution culture with N supplied as 20 mM NH4NO3 and pre‐treated by extending the 11 h photosynthetically significant light period either by 1 h (short‐day or SD pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These increased N pools in the grass leaves seemed to be correlated with slightly increasing NO − 3 and NH + 4 concentrations in the soil. Several authors have reported that during the first days after cutting, uptake of N is inhibited (Bakken et al, 1998;Ourry et al, 1988). In such case, plants respond by allocating N from reserves in root and stubble to the developing leaves.…”
Section: Discussionmentioning
confidence: 99%
“…These increased N pools in the grass leaves seemed to be correlated with slightly increasing NO − 3 and NH + 4 concentrations in the soil. Several authors have reported that during the first days after cutting, uptake of N is inhibited (Bakken et al, 1998;Ourry et al, 1988). In such case, plants respond by allocating N from reserves in root and stubble to the developing leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in these N pools was paralleled by slightly increasing NO − 3 and NH + 4 concentrations in the soil. Several authors have reported that during the first days after cutting, uptake of N is inhibited (Bakken et al, 1998;Ourry et al, 1988). In such case plants respond by allocating N from reserves in root and stubble to the developing leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Reserve N accumulation is not limited to perennial legumes. Uptake of nitrate and ammonium from the soil by forage grasses is severely reduced by defoliation in summer ( Bakken et al, 1998 ; Louahlia et al, 1999 ). These plants mobilize leaf sheath and root N pools to regrowing leaf blades ( Ourry et al, 1989 , 1990 ).…”
Section: Introductionmentioning
confidence: 99%